Evaluation of antioxidant enzyme activity and antioxidant capacity in patients with newly diagnosed pemphigus vulgaris. (16th February 2015) - Javanbakht, M. H.; Djalali, M.; Daneshpazhooh, M.; Zarei, M.; Eshraghian, M. R.; Derakhshanian, H.; Chams‐Davatchi, C.
Summary Background Pemphigus vulgaris (PV) is an autoimmune blistering disorder of the skin and/or mucosa. Increased levels of reactive oxygen species (ROS) were previously reported in PV. Aim Because oxidative stress has an important role in the inflammatory process, we designed this study to evaluate the antioxidant status in patients with PV and to compare it with that of healthy controls (HCs). Methods In this case–control study, 43 newly diagnosed patients with PV were compared with 58 HCs. The severity of the disease was estimated according to Harman scores. Erythrocyte glutathione peroxidase (GPx), superoxide dismutase (SOD), CAT and serum malondialdehyde (MDA) activities and total antioxidant capacity were measured. Data were analyzed by independent t‐test. Results Both groups were similar in sex, age and body mass index. Mean duration of disease was 5.6 months. Mean oral and skin severities were 1.79 and 2.3 respectively, based on Harman scores. SOD activity was not significantly different between groups (1003.30 ± 39.96 vs. 1009.76 ± 32.68 U/gHb). Levels were noticeably higher in patients with PV than in HCs for both GPx (52.13 ± 2.85 vs. 36.63 ± 1.49 U/gHb, respectively; P < 0.001) and CAT (205.69 ± 8.10 vs. 130.26 ± 6.80 kU/gHb, respectively; P < 0.001) activities, and CAT activity correlated with disease severity. In addition, patients had lower total antioxidant capacity than controls (3.39 ± 0.06 vs. 3.72 ± 0.09 mmol/L, P = 0.006). There was no noticeable difference in serum MDA between the two groups (P = 0.45). Conclusions Patients with PV have significantly higher antioxidant enzyme activities and lower total antioxidant capacity compared with HCs. These data indicate the importance of improving antioxidant level in patients with pemphigus.